Classroom-Based Motivational Interviewing for Improving College Students' Academic Performance: A Randomized Trial. (April 2019) - Strait, Gerald G.; Williams, Christopher; Peters, Christopher
In this study, we used a randomized control trial ( N = 84) to evaluate the effects of a classroom-based motivational interviewing intervention on undergraduate psychology students' test performance. Results indicated that students in the treatment group ( n = 38) demonstrated significant increases in their exam grades following the intervention ( d = .34). However, these changes were not significantly different from students in a control group ( n = 43) who received a handout on study tips.